The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/cdli.9.6.1372-1375.2002
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Cytokines, Soluble Interleukin-2 Receptor, and Soluble CD30 in Sera of Patients with Hepatitis B Virus Infection during Acute and Convalescent Phases

Abstract: The immunoregulatory roles of interleukin-2 (IL-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…One cannot discard, however, the possibility that besides the hypothesis of the existence of a defect in the generation of cGMP, other sources of could be contributing to its serum level via the expression of induced NO-synthase by inflammatory cells (macrophages, neutrophils, and vascular muscle cells, among others). Furthermore, the findings of raised levels of sIL-2R in diabetic patients are in accordance with those reported by Doganay et al [ 17 ] and this indicates activation of T lymphocytes [ 18 ]. Taken together, these findings suggest that this group of diabetic patients present a low-grade inflammation triggered by the diabetic mellitus state, which is favouring the progression of accelerated atherosclerosis.…”
Section: Discussionsupporting
confidence: 91%
“…One cannot discard, however, the possibility that besides the hypothesis of the existence of a defect in the generation of cGMP, other sources of could be contributing to its serum level via the expression of induced NO-synthase by inflammatory cells (macrophages, neutrophils, and vascular muscle cells, among others). Furthermore, the findings of raised levels of sIL-2R in diabetic patients are in accordance with those reported by Doganay et al [ 17 ] and this indicates activation of T lymphocytes [ 18 ]. Taken together, these findings suggest that this group of diabetic patients present a low-grade inflammation triggered by the diabetic mellitus state, which is favouring the progression of accelerated atherosclerosis.…”
Section: Discussionsupporting
confidence: 91%
“…By in vitro and in vivo studies, it has been shown that these inflammatory cells especially cytotoxic T‐lymphocytes produce a number of cytokines including TNF‐α and IFN‐γ which mediate the inflammatory process and contribute to the successful clearance of the virus. Additionally, these cytokines are also produced by injured endogenous cells, such as kuppfer cells, endothelial cells, hepatocytes and bile duct epithelial cells (1,6,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…In children, sIL‐2R has been used as a diagnostic or prognostic marker of various immunological disorders, such as refractory Kawasaki disease, hemophagocytic syndrome, and macrophage activation syndrome caused by systemic juvenile idiopathic arthritis . It was also reported that the serum level of sIL‐2R is elevated in patients with acute hepatitis B virus infection . Lobo‐Yeo et al .…”
Section: Discussionmentioning
confidence: 99%